Dissolution kinetics of silver nanoparticles: Behaviour in simulated biological fluids and synthetic environmental media. (2022) - Mbanga, Odwa; Cukrowska, Ewa; Gulumian, Mary
Abstract: Silver nanoparticles offer a wide range of benefits including their application in several fields such as medical, food, health care, consumer, and industrial purposes. However, unlocking this potential requires a responsible and co-ordinated approach to ensure that potential challenges emanating from the use of silver nanoparticles are being addressed. In this study body fluids and environmental media were used to investigate the effects of citrate coated silver nanoparticles (cit-coated AgNPs) to mimic their behaviour in real life situations. Understanding the dissolution kinetics and behaviour of cit-coated AgNPs in simulated biological fluids and synthetic environmental media helps us predict their fate and effects on human health and the environment. The cit-coated AgNPs behaviour significantly varied in acidic and alkaline simulated fluids. Low pH and high ionic strength accelerated the rate and degree of dissolution of AgNPs in simulated fluids. Following exposure to simulated fluids cit-coated AgNPs demonstrated significant changes in agglomeration state and particle reactivity however, the morphology remained unaltered. The slow dissolution rates observed for highly agglomerated cit-coated AgNPs in simulated blood plasma, Gamble's and intestinal fluids, and freshwater indicate that there is a greater likelihood that the particles will be the cause of the observed adverse effects. In contrast, the fast dissolution rates observed for cit-coated AgNPs in simulated gastric and phagolysosomal fluid and synthetic seawater, the release of the silver ions at a fast rate, will be the cause of their short-term effects. Graphical Abstract: ga1 Highlights: Understanding the dissolution kinetics of AgNPs to predict their effects on human health and the environment. Low pH and high ionic strength accelerated the rate and degree of dissolution of AgNPs in simulated fluids. AgNPs demonstrated significant changes in agglomeration state upon exposure to simulated fluids. Fast dissolution rates observed for AgNPs in simulated acidic fluids & will be the cause of their short-term effects.